Nutritional Status and Quality of Life of Hemodialysis Patients in a Hospital in Yogyakarta - Siswandi, Siswandi; Suhendra, Gugun; Wulandari, D; Simanjuntak, LB; Dania, Haafizah; Irham, Lalu Muhammad; Faridah, Imaniar; Adnan, Adnan; Perwitasari, Dyah Aryani (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Kidney failure is a disease with a moderate prevalence in Indonesia but causes the second highest cost burden in Indonesia. One of the treatments for chronic kidney failure is hemodialysis. The problem with hemodialysis patients is a high incidence of malnutrition, which can affect the patient's quality of life. Therefore, this study will examine the relationship between nutritional status and quality of life in chronic kidney failure patients undergoing hemodialysis. This research is a cross-sectional study by collecting medical record data and filling out questionnaires. Selection of research subjects with inclusion criteria aged ≥18 years, routinely undergoing hemodialysis, willing to participate in the study and complete medical record data. The patient's nutritional status was seen from the Body Mass Index (BMI), and the patient's quality of life was assessed by the Indonesian version of the Kidney Disease Quality of Life Short-Form (KDQoL-SFTM) questionnaire. The average age of the hemodialysis patients in this study was 53.70 years, the average body weight was 57.24 kg and the average height was 10.82 cm. Patients with lean BMI were 20.5%, normal 56.4%, overweight 23.1%, and obesity 2.6%. The domain of employment status is related to nutritional status (p-value 0.005). Nutritional status is related to the quality of life of hemodialysis patients in the occupational status domain.